Phonetic Contrast and its Importantce in Translation: The Arabic-Spanish Case: التّقابل الصّوتي وأهميته في الترجمة "عربي إسباني" أنموذجا" - Felli , Zineb (Maalim, 2026)
This study examines the phonetic contrast between Arabic and Spanish and its importance in translation. It aims to highlight the role of contrastive phonetic studies in facilitating translation between the two languages. The research identifies the main similarities and differences in their sound systems in order to predict possible errors made by translators or learners of Arabic. The study adopts a descriptive, analytical, and contrastive approach. The results show that phonetic contrast contributes to improving translation accuracy by anticipating potential difficulties. They also reveal significant differences between the two languages despite some similarities in articulation. Spanish lacks pharyngeal and emphatic sounds that exist in Arabic. These findings emphasize the importance of phonetic awareness in Arabic–Spanish translation.